Uses and abuses of recovery: implementing recovery‐oriented practices in mental health systems. Issue 1 (4th February 2014) - Slade, Mike; Amering, Michaela; Farkas, Marianne; Hamilton, Bridget; O'Hagan, Mary; Panther, Graham; Perkins, Rachel; Shepherd, Geoff; Tse, Samson; Whitley, Rob
<x xml:space="preserve">Abstract</x> An understanding of recovery as a personal and subjective experience has emerged within mental health systems. This meaning of recovery now underpins mental health policy in many countries. Developing a focus on this type of recovery will involve transformation within mental health systems. Human systems do not easily transform. In this paper, we identify seven mis‐uses ("abuses") of the concept of recovery: recovery is the latest model; recovery does not apply to "my" patients; services can make people recover through effective treatment; compulsory detention and treatment aid recovery; a recovery orientation means closing services; recovery is about making people independent and normal; and contributing to society happens only after the person is recovered. We then identify ten empirically‐validated interventions which support recovery, by targeting key recovery processes of connectedness, hope, identity, meaning and empowerment (the CHIME framework). The ten interventions are peer support workers, advance directives, wellness recovery action planning, illness management and recovery, REFOCUS, strengths model, recovery colleges or recovery education programs, individual placement and support, supported housing, and mental health trialogues. Finally, three scientific challenges are identified: broadening cultural understandings of recovery, implementing organizational transformation, and promoting citizenship.